A worldwide investigation of critical care research coordinators' self‐reported role and professional development priorities: the winner survey. Issue 5 (8th October 2012) - Eastwood, Glenn M; Roberts, Brigit; Williams, Ged; Rickard, Claire M
<x xml:space="preserve">Abstract</x> Aims and objectives. To describe the self‐reported role and professional development priorities of research coordinators in different regions of the world. Background. Research coordinators employed in critical care settings provide clinical and technical expertise in the development, conduct and completion of clinical research studies. Knowledge of this specialised role is well established in some parts of the world, yet emerging in others. Design. Descriptive exploratory study involving research coordinators outside of Australia and New Zealand. Method. An anonymous, structured, multiple‐choice, web‐based questionnaire conducted between April–May 2011. Results. There were 80 respondents from North America (61%), Europe (29%) and Latin America (10%). The majority of respondents performed data collection and obtained informed consent, and half had presented study findings at conferences or wrote scholarly articles, despite a greater willingness to do so. Requisite skills for the research coordinator role included clinical research knowledge, creative problem solving and the ability to identify/resolve ethical questions. 'Best' reported aspects of the role were promotion of evidence‐based clinical practice, intellectual stimulation and autonomy. 'Worst' aspects included heavy workload, lack of funding and recognition. Conclusion. Research coordinators working in critical care settings collect data, require clinical research knowledge and problem‐solving skills and are interested in, but have less confidence in, dissemination of research findings. They feel isolated with a lack of support and inadequate remuneration for the effort and time required to maintain the high standards of their role. This is outweighed by the satisfaction derived from promoting the research process and autonomy. Further observational studies aimed at clarifying and advancing the role of the research coordinator is warranted. Relevance to clinical practice. This study offers insight into the global roles and responsibilities as reported by research coordinators employed in critical care settings.